Submental liposuction for the management of lymphedema following head and neck cancer treatment: a randomized controlled trial - Uthman Alamoudi; Benjamin Taylor; Colin MacKay; Matthew H. Rigby; Robert Hart; Jonathan R. B. Trites; S. Mark Taylor (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients who have undergone treatment for head and neck cancer are at risk for neck lymphedema, which can severely affect quality of life. Liposuction has been used successfully in cancer patients who suffer from post-treatment limb lymphedema. The purpose of our study was to review the outcomes of head and neck cancer patients at our center who have undergone submental liposuction for post-treatment lymphedema and compare their subsequent results with a control group. Methods All head and neck cancer patients at an oncology center in tertiary hospital setting who complained to their attending surgeon or radiation oncologist regarding cervical lymphedema secondary to head and neck cancer treatment, and had been disease-free for a minimum of one year, with no previous facial plastic surgical procedures were eligible for inclusion into the study. Study design was a non-blinded randomized controlled trial. Twenty patients were randomized into a treatment arm (underwent submental liposuction n = 10) and control arm (n = 10). Both groups of patients completed two surveys (Modified Blepharoplasty Outcome Evaluation and the validated Derriford Appearance Scale) on initial office visit after consenting for the trial. The treatment group then completed the surveys 6 months post-operatively while the control group filled the surveys 6 months after the initial assessment but had no intervention. Mann-Whitney U tests were performed to compare the responses of those that did and did not receive liposuction. Results Our study demonstrated a statistically significant improvement in patients’ self-perception of appearance and statistically significant subjective scoring of appearance following submental liposuction. Conclusions Submental liposuction is an effective and safe procedure to improves the quality of life for head and neck cancer patients suffering from post-treatment lymphedema.